Tingkat Kinerja Penyuluh Pada Kelompok Tani Padi Sawah di Desa Bumi Raya Kecamatan Andoolo Kabupaten Konawe Selatan - Sutriani, Ni Wayan; Arimbawa, Putu; Abdullah, Sukmawati (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
At Village Earths Raya up to 3 (three) the last year experiences changing, far ranging farm sawah that at o year 2014 which is 227,15 Ha overbids than previous years which is 212,47 Ha. This picture points out the importance for optimalisasi extension agent performance, in builds and adjoining and motivates farmer to optimize farm and production exploit and farming productivity. This research intent to know and describes extension agent performance zoom on agglomerate tani sawah's paddy at Silvan Raya's Earth Andoolo's district Konawe's Regency south. Sample determination is done with method Purposive , Total observational sample 11 respondents consisting of 10 respondents of tani's groups and 1 of agricultural extension agents. This data at o by use of Analisis Interval. The result oft this study indicate that fisher extension agent at Silvan Raya's Earth cover counselling main activity (training,course, and visit), giving counselling material, teaching method and good Counselling media to tani's group, and gives science about development aspect self have positive percentage (well) or as much 63,7 %. Just extant performance which adverse on main activity indicator counselling which is training activity and course that still performing amount reducing it.